Media Discursive Strategy of CNN Indonesia and Republika.co.id in Representing Jihad and Shahid: A Corpus-Based Critical Discourse Analysis Approach - Fahad, Malik; Roselani, Ni Gusti Ayu (Al-Lisan: Jurnal Bahasa, 2025)
Background: The mass media play a crucial role in constructing social reality through language selection and issue framing. One significant issue concerns the representation of jihad and shahid, which are framed differently by CNN Indonesia and Republika.co.id. Aims: This study aims to examine how CNN Indonesia and Republika.co.id construct the meanings of jihad and shahid across various news topics and to investigate the discursive strategies they employ in linking these concepts within their news coverage. Methods: This study adopted a mixed-methods approach, combining qualitative and quantitative analyses. Fairclough's critical discourse analysis was applied to explore the discursive strategies used by the mass media to construct and reinforce ideology, stereotypes, prejudice, and discrimination in the representation of jihad and shahid. The research employed the AntConc corpus tool for keyword analysis, collocation, and concordance. The dataset consisted of news articles containing the terms jihad and shahid, published over the past eight years on CNN Indonesia and Republika.co.id. Results: The findings reveal that CNN Indonesia and Republika.co.id play a significant role in shaping public discourse and perceptions of jihad and shahid in Indonesia. The media frequently associate these terms with Islam, radicalism, and terrorism, often leading to generalized and oversimplified interpretations. CNN Indonesia tends to reinforce negative stereotypes and prejudices against Islam, whereas Republika.co.id presents a more positive interpretation. Implications: This study underscores the critical role of media in shaping social and cultural understandings of religious concepts. The findings highlight the need for more nuanced and balanced media representations to prevent the perpetuation of stereotypes and to promote a more inclusive and informed public discourse on sensitive issues such as jihad and shahid.